From Marco Polo Bridge to Pearl Harbor : who was responsible? - Auer, James E.; Watanabe, Tsuneo, 1926- (The Yomiuri Shimbun, 2010)
Japan's Yomiuri newspaper has undertaken a bold project, the first of its kind in the Japanese intellectual community since the end of World War II. Yomiuri seriously probes the outbreak and prolongation of the wars of the Showa Era and examines the responsibility of many Japanese political leaders and high-ranking military officers, including some not tried in the Tokyo Tribunal, such as Prince Konoe and Army Minister Anami. Yomiuri's scrutiny is pioneering, comprehensive and courageous.